Determinants of online open access databases towards academic career advancement: a conceptual study / Hafisah Yaakob ...[et al.] - Yaakob, Hafisah; Mahyideen, Jamilah Mohd; Mohamad Rusli, Nurhanani Aflizan; Mohamad, Wan Normila; Mohamad Gobil, Abdul Rahman (Universiti Teknologi MARA, 2021)
In this age of modern technology, people worldwide utilise many websites to learn or extract information more about an organisation remotely. Websites are a very effective platform for disseminating information to the public. Most universities use this platform to share information with large audience. The information presented on the official website of an organisation should be relevant, recent, and accessible to the public. These databases are overseen by the academic communities for teaching and learning, research collaboration, and career advancement. This conceptual study aims to explain the importance of a database of lecturers' expertise towards their career advancement. The volume of the database of lecturer expertise described in this study can be divided into two categories: university website and academic staff visibility. Universities must develop a database of these lecturers' expertise which shall be linked to the existing university's website to enable the public to access recent and relevant information. By having dynamic website contents, records related to lecturers' expertise shall be created, read, updated, and deleted (CRUD) from time to time.